2023
DOI: 10.1021/acsmaterialslett.2c01044
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Derived Fibrin Hydrogels Containing Graphene Oxide for Infections Treatment

Abstract: Wound infection is inevitable in most patients suffering from extensive burns or chronic ulcers, and there is an urgent demand for the production of bactericidal dressings to be used as grafts to restore skin functionalities. In this context, the present study explores the fabrication of plasma-derived fibrin hydrogels containing bactericidal hybrids based on graphene oxide (GO). The hydrogels were fully characterized regarding gelation kinetics, mechanical properties, and internal hydrogel structures by disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…A similar FTIR pattern has been reported for CDs prepared hydrothermally from citric acid and ethylenediamine. 39 Next, in the XRD pattern of the crystalline phase of CDs, peaks were observed at 11.08, 26.92, and 28.5 (Fig. 1(f)).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…A similar FTIR pattern has been reported for CDs prepared hydrothermally from citric acid and ethylenediamine. 39 Next, in the XRD pattern of the crystalline phase of CDs, peaks were observed at 11.08, 26.92, and 28.5 (Fig. 1(f)).…”
Section: Resultsmentioning
confidence: 93%
“…Hydrogels have drawn a great deal of interest with a wide range of possible medical, pharmacological, and prosthetic uses. 38,39 Hydrogels are three-dimensional hydrophilic polymer networks that hold a significant fraction of water. 40 Hydrogels have capacity to absorb water and their swelling and permeability characteristics facilitate their direct biological use.…”
Section: Introductionmentioning
confidence: 99%
“…All dispersions showed antibacterial capacity against both strains, but a more significant effect was evident against B. subtilis , as more extensive inhibition areas were observed on plates grown with this strain compared to those with E. coli . The antibacterial studies were also performed using the plate test, as previously reported in the literature [ 20 , 42 ]. The antibacterial capacity was measured by quantifying the area of bacterial growth ( Figure S7 ) using the ImageJ program, and the results obtained for both strains are shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…GO is a well-known two-dimensional graphene-based nanomaterial (GBN) with large surface area and excellent biocompatibility, generally due to its surface being decorated with oxygen-containing groups [ 17 , 18 ]. At the same time, various hypotheses on the bactericidal impact of GBNs, in general (i.e., the nanoblade effect, envelope, or oxidative stress induction), have been presented in the literature [ 19 , 20 , 21 ]. On the other hand, ZnO nanoparticles, reported by several studies as non-toxic to human cells [ 22 ], also exhibit antibacterial activity through different mechanisms such as the destabilization of microbial membranes upon the direct contact of ZnO particles to the cell walls [ 23 ], the generation of reactive oxygen species [ 24 , 25 ], or the release of zinc ions that disrupt bacterial membrane integrity and interfere with cellular processes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 More recently, we synthesized plasma-derived fibrin hydrogels containing the bactericidal GO/STREP hybrid for sustained antibiotic release, demonstrating significant potential for future fabrication of bactericidal skin equivalents for wound healing and treating extensively burnt patients. 18 In a different study, a novel bioink made of plasma, alginate, and methylcellulose was presented as a promising material for several forms of bioprinted tissue equivalents; it proved to be exceptionally advantageous when combined with calcium phosphate cement, enhancing the biofabrication of bone-like constructs. 19 However, finding a biocompatible matrix that can host fibroblasts and that can, per se, enhance cell proliferation is still challenging.…”
Section: Introductionmentioning
confidence: 99%